IMPLEMENTASI METODE MAUIZAH HASANAH DALAM MENINGKATKAN KECERDASAN INTERPERSONAL ANAK KELOMPOK B TK ISLAM JAYAWINATA KOTA TANGERANG - Kurnia Akbar; Rifqiyah Mulia Azmi (Fakultas Tarbiyah IIQ Jakarta, 2024)
The purpose of this study was to find out the implementation of the mauizah hasanah method in improving the interpersonal intelligence of group B children This research is a type of field research with a qualitative research approach. The data collection techniques were obtained through observation, interviews and documentation. After the data is collected, it is then analyzed through data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the mauizah hasanah method in improving the interpersonal intelligence of group B children at Jayawinata Islamic Kindergarten is very effective and good, as evidenced by the achievement of interpersonal skills of TK B children in socializing and communicating with the surrounding environment. The factors that affect children's interpersonal intelligence are influenced by environmental factors around the child, such as parents, nutrition, and the stimulus provided.